Fibrosis in PCLS: comparing TGF-β and fibrotic cocktail - Carlos Machahua; Thomas M. Marti; Patrick Dorn; Manuela Funke-Chambour (Respiratory Research)
Abstract Introduction Fibrotic cocktail (FC) is a combination of pro-fibrotic and pro-inflammatory mediators that induces early fibrotic changes in organotypic lung models. We hypothesised that transforming growth factor beta 1 (TGF-β1) alone induces a pro-fibrotic effect similar to FC. Our aim was to compare the pro-fibrotic effects of TGF-β1 with FC in human precision-cut lung slices (PCLS). Methods PCLS from “healthy” lung tissue of cancer patients undergoing surgery (n = 7) were incubated with TGF-β1, FC or control for 72 h. Gene expression markers for myofibroblasts differentiation, extracellular matrix (ECM), as well as TGF-β receptors were assessed (RT-qPCR). ECM proteins expression in lysates and supernatant was assessed by ELISA and immunofluorescence. Results We found that TGF-β1 significantly increased gene expression of ACTA2, COL1A1, CCN2, and VIM compared to control but also compared to FC. FC showed a significant increase of matrix metalloproteinase (MMP) 7 and 1 compared to control, while TGF-β receptor 2 was lower after FC compared to TGF-β1 or control. FC or TGF-β1 showed similar fibronectin protein expression in lysates and supernatants, while type I collagen protein expression in lysates was significantly greater with TGF-β1 compared to control. Conclusions Our findings show that TGF-β1 induces consistent pro-fibrotic changes in PCLS after 72 h. Compared to TGF-β1, FC treatment resulted in reduced gene expression of TGF-β receptor 2 and increased MMPs expression, potentially mitigating the early pro-fibrotic effects. Selecting specific pro-fibrotic stimuli may be preferable depending on the research question and time point of interest in lung fibrosis studies using PCLS.